The Effect Of Corporate Social Responsibility As A Deductible Expense On Tax Aggressiveness - Leviany, Tevi; Dwi, Rima; Sukadwilinda, Sukadwilinda; Murni, Ineke Dyah Setia (Adpebi Science Series, 2023)
The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) as a deductible expense on tax aggressiveness. The independent variable in this study is CSR, which is measured using CSR disclosure based on the components of CSR-related costs that may be deductible to gross income (deductible expense) as stated in Law Number 36 of 2008 concerning Income Tax. Control varable in this study is capital intensity, while the dependent variable used is tax aggressiveness as measured by the effective tax rate. The regression model used in this study is the panel data regression model, which was processed using eviews software version 13. The research sample was selected using a purposive sampling method and obtained 60 sample food and beverage sub-sector manufacturing companies that meet the criteria and are listed on the Indonesia Stock Exchange (IDX) for the period 2018–2021. The research results obtained show that Corporate Social Responsibility (CSR) and capital intensity have no effect on tax aggressiveness.